2005
DOI: 10.1097/01.jom.0000165748.31326.e8
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Health Effects Related to Occupational Spray Painting and Welding

Abstract: Welders and painters in this plant appeared to have increased risk of respiratory health effects compared with assembly workers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 25 publications
1
21
0
Order By: Relevance
“…Mastrangelo et al [2003] observed a significant association between COPD and painting. It may be the case that specific paints confer the risk of COPD; Pronk et al [2007] observed an association between COPD-like symptoms and exposure to spray paints containing hexamethylene diisocyanate, and a significantly increased risk of physiciandiagnosed COPD (OR ¼ 3.73, 95% CI ¼ 1.27-11.0) was observed by Hammond et al [2005] in their cross-sectional study of automotive workers doing painting. We were not able to evaluate isocyanate-based paint exposures separately in our analyses due to the low frequency of this reported exposure in our population (0.8% of workers).…”
Section: Discussionmentioning
confidence: 89%
“…Mastrangelo et al [2003] observed a significant association between COPD and painting. It may be the case that specific paints confer the risk of COPD; Pronk et al [2007] observed an association between COPD-like symptoms and exposure to spray paints containing hexamethylene diisocyanate, and a significantly increased risk of physiciandiagnosed COPD (OR ¼ 3.73, 95% CI ¼ 1.27-11.0) was observed by Hammond et al [2005] in their cross-sectional study of automotive workers doing painting. We were not able to evaluate isocyanate-based paint exposures separately in our analyses due to the low frequency of this reported exposure in our population (0.8% of workers).…”
Section: Discussionmentioning
confidence: 89%
“…This difference in PRs may be related to poor hygiene, habitation, nutrition, and work environment. Spice factory workers [Zuskin et al,1988] Women 27.2 Fruit-bottling workers 2.9 <0.01 Hemp workers [Zuskin et al,1990] All 33.3 Packersinfoodindustry 6.7 <0.01 Glassblowers [Zuskin et al,1993] Men 28.8 Clerks 3.8 <0.001 Wool textile workers [Zuskin et al,1995] Men 62.1 Delivery workers 2.3 <0.01 Women 43.0 Delivery workers 3.4 <0.01 Garage workers [Bener et al,1998] All 26.6 Taxi drivers 16.4 <0.03 Paper-recycling workers [Zuskin et al,1998a] Men 31.7 Packersinfoodindustry 2.3 <0.01 Synthetic textile workers [Zuskin et al,1998b [Hammond et al, 2005] All 32.5 Painters [Hammond et al, 2005] All 37.1…”
Section: Discussionmentioning
confidence: 98%
“…Several scientific studies have shown these symptoms to be prevalent in welders. 13,14,15,16,17 These are attributed to the various irritant and sensitizing gases and particles of metals that constitute welding fumes. 18 Therefore, reduction of exposure to these agents may lead to a resultant decrease in the prevalence of these symptoms.…”
Section: Discussionmentioning
confidence: 99%